Weed Management Principles in Commercial Vegetable Production - Peter Dittmar; Nathan Boyd (EDIS)
Weeds compete with vegetable crops for light, water, and nutrients. This competition decreases plant vigor, yield, and crop quality. They interfere with hand harvest and can complicate or prevent machine harvest. Weeds also serve as alternative hosts to diseases, viruses, and nematodes. A successful weed management program will incorporate multiple control practices with preventative, cultural, biological, mechanical, and chemical methods. This revised 6-page fact sheet was written by Peter Dittmar and Nathan Boyd, and published by the UF Department of Horticultural Sciences, July 2014.